2022
DOI: 10.3389/fnut.2022.749948
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Supplementation Reverses Tenofovir-Caused Bone Mineral Density Loss in People Taking ART or PrEP: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe decrease of bone mineral density (BMD) after the intake of Tenofovir disoproxil fumarate (TDF)-based drugs in people living with HIV/AIDS (PLWHA) and HIV-negative key populations under pre-exposure prophylaxis (PrEP) regimen raised concerns. Previous findings on the effects of vitamin D (VD) and calcium supplements and the recovery of BMD loss were inconclusive. The optimal doses of VD and calcium and its supplementary duration remained unknown. Therefore, we conducted a systematic review and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, some experts suggest a spinal X-ray annually after TDF initiation to detect early bone abnormalities [13]. Of note, a meta-analysis of seven studies that included more than 700 participants reported statistically significant improvement in BMD with a mean difference of 0.4 points when supplemental vitamin D and calcium were prescribed to patients on TDF as an additional strategy to minimize the negative impact of TDF on BMD [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some experts suggest a spinal X-ray annually after TDF initiation to detect early bone abnormalities [13]. Of note, a meta-analysis of seven studies that included more than 700 participants reported statistically significant improvement in BMD with a mean difference of 0.4 points when supplemental vitamin D and calcium were prescribed to patients on TDF as an additional strategy to minimize the negative impact of TDF on BMD [15].…”
Section: Discussionmentioning
confidence: 99%
“…In real-world data, Fanconi syndrome incidence has ranged between one and five per 1,000 patients receiving TDF [13,14]. Although more than 50% of Fanconi syndrome cases are resolved within the first year following TDF discontinuation [15,16], delayed recovery has been observed in some cases [17]. Herein, we report a case of TDF-associated Fanconi syndrome, which resulted in bone mass loss and fragility fracture approximately four years following TDF discontinuation.…”
Section: Introductionmentioning
confidence: 92%
“…The possible use of vitamin D and calcium to lower PTH and increase bone mineral density has been suggested, and some short‐term positive effects of vitamin D therapy with and without calcium supplementation have been demonstrated. ( 39 , 40 ) However, the benefits of vitamin D supplementation in individuals with good vitamin D status are unknown, and unexpected long‐term effects of calcium supplementation in African women and children have been reported. ( 41 ) Thus, further studies are needed to explore mechanisms in more detail and to investigate whether the use of TDF‐based ART by African women during pregnancy and lactation has long‐term consequences for the bone health of the mother and for the growth of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Summary of evidence: A systematic review and meta-analysis of people with and without HIV using tenofovir disoproxil fumarate as part of ART or PrEP, respectively, reported that vitamin D supplementation was correlated with improved BMD. 109 A randomized, double-blind, placebo-controlled study assessing vitamin D and calcium supplementation in ART-naive people with HIV initiating efavirenz/emtricitabine/tenofovir disoproxil fumarate reported smaller declines in total hip and lumbar spine BMD in participants receiving high-dose vitamin D and calcium. 110 An analysis of people with HIV taking dolutegravir-based ART in the prospective observational SCOLTA Project found that vitamin D supplementation was associated with improved BMD.…”
Section: Consensus Statementsmentioning
confidence: 99%